Cardiovascular effects of 6-nitrodopamine, adrenaline, noradrenaline, and dopamine in normotensive and hypertensive rats - Fuguhara, Vivian; De Oliveira, Mariana Gonçalves; Aguiar da Silva, Carlos Alberto; Guazzelli, Pedro Renato; Peterson, Larryn W.; De Nucci, Gilberto (Frontiers in Pharmacology, 2025)
Introduction6-Nitrodopamine (6-ND) has been extensively investigated using in vitro protocols, especially in the cardiovascular system. Despite the established more potent positive chronotropic and inotropic effects, in comparison with the classical catecholamines, adrenaline (ADR), noradrenaline (NA) and dopamine (DA), the effects with in vivo models are not determined yet. Here, we investigated the acute effects on heart rate (HR) and mean arterial blood pressure (MABP) in normotensive and hypertensive rats by 6-ND.MethodsAdult male Wistar rats were randomly divided into two groups: one received regular filtered water and the other a chronic Nω-nitro-L-arginine methyl ester (L-NAME) treatment in the water (20mg/day/rat, 4weeks). Thereafter, the animals were anesthetized, the HR and MABP were monitored through the femoral artery, and the vein was used to administer bolus injections of 6-ND, ADR, NA and DA. Moreover, 6-ND, classical and novel catecholamines, 6-cyanodopamine (6-CYANO), 6nitroadrenaline (6-NADR), and 6-nitrodopa (6-NDOPA) were used to assess their effect on monoamine oxidase (MAO) activity.ResultsAll four drugs significantly increased the HR in control animals; 6-ND was more potent than the classical catecholamines and its positive chronotropic effect was abolished with the chronic L-NAME treatment. Furthermore, in a cell-free assay, 6-ND was able to partially inhibit MAO-A (<30% at 1 mM) and MAO-B (<40% at 10 μM); 6-NDOPA and 6-CYANO (1 mM) inhibited MAO-A, and MAO-B by around 40%, respectively. ADR produced MAO-A inhibition of <20%, at 100μM.ConclusionsThese results clearly demonstrate that 6-ND is the most potent endogenous positive chronotropic agent yet described, and its effects are independent of MAO inhibition.